TAMI-60. MODULATION OF CELL BIOMECHANICS THROUGH GUIDANCE RECEPTOR PLEXIN-B2 FACILITATES GLIOBLASTOMA INFILTRATION. (12th November 2021) - Friedel, Roland; Huang, Yong; Tejero, Rut; Alves, Chrystian Junqueira; Brusco, Concetta; Hannah, Theodore; Lee, Vivian; Dai, Guohao; Zou, Hongyan
Abstract: Infiltrative growth is a major cause of the high lethality of malignant brain tumors such as glioblastoma (GBM). The study of the contribution of biomechanical processes to GBM invasion is an emerging field. We show here that GBM cells upregulate the guidance receptor Plexin-B2 to gain invasiveness by modulating their biomechanical properties. Deletion of Plexin-B2 in GBM stem cells limited tumor spread and shifted invasion paths from axon fiber tracts to perivascular routes. On a cellular level, Plexin-B2 adjusts cell adhesiveness, migratory responses to different matrix stiffness, and actomyosin dynamics, thus empowering GBM cells to leave stiff tumor bulk and infiltrate softer brain parenchyma. Correspondingly, gene signatures affected by Plexin-B2 were associated with locomotor regulation, matrix interactions, and cellular biomechanics. On a molecular level, the intracellular Ras-GAP domain contributed to Plexin-B2 function, while the signaling relationship with downstream effectors Rap1/2 appeared variable between GBM stem cell lines, reflecting intertumoral heterogeneity. Our studies have established Plexin-B2 as a modulator of cell biomechanics that is usurped by GBM cells to gain invasiveness. Ongoing investigations focus on the regulation of the biomechanical properties of cell membrane and cell actomyosin cortex through plexins that provide GBM cells with the mechanical dynamics to penetrate to restricted space.